Material–Structure–Function Integrated Additive Manufacturing of Degradable Metallic Bone Implants for Load‐Bearing Applications. (5th February 2023) - Zhao, Danlei; Yu, Keda; Sun, Tingfang; Jing, Xirui; Wan, Yizhou; Chen, Kaifang; Gao, Hairui; Wang, Yifan; Chen, Lili; Guo, Xiaodong; Wei, Qingsong
Abstract: The integration of bio‐adaptable performance, elaborate structure, and biological functionality for degradable bone implants is crucial in harnessing the body's regenerative potential to remold load‐bearing bone defects. Herein, material–structure–function integrated additive manufacturing (MSFI‐AM) is deployed to innovate novel zinc‐based bone implants, namely Zn–Mg–Cu alloy. In situ alloying of AM and boundary engineering strategy yield prominent mechanical properties, and the degradation products enable a mechanical self‐strengthened effect, thus coordinating mechanical degeneration and promoting mechanical adaptability. In addition, MSFI‐oriented Zn alloy implants successfully manifest in situ multifunctions of augmenting osteogenesis, immunoregulation, angiogenesis, and anti‐infective activity in vitro and expediting bone ingrowth and regeneration in vivo through the sustained release of divalent metal cations and triply periodic minimal surface (TPMS) structure construction. Overall, MSFI‐AMed Zn alloy implants signify promising clinical translation prospects for load‐bearing applications, and an integrated approach is proposed to endow degradable bone implants with boosted bio‐adaptable performance and in situ bio‐multifunctions. Abstract : This study develops a material–structure–function integrated additive manufacturing (MSFI‐AM) strategy that combines bio‐adaptable performance, elaborate structure, and biological functionality for degradable metallic bone implants. Superior mechanical adaptability and excellent in vitro and in vivo performances of MSFI‐oriented Zn alloy scaffolds signify promising clinical translation prospects for load‐bearing applications.